Mobile technology for older people: use of personas - Abd Malik, Sofianiza; Azuddin, Muna (2013)
This paper is concerned with the use of mobile phone by Malaysian older people and the main focus was the appropriate methods for collecting data. There are a number of problems with conventional techniques when using older people as participants. This was due to the fact that older people had an extremely wide range of characteristics and impairments compared to other groups. It seemed that there should be more techniques adapted and used in gathering user requirements for mobile phone and older people. In fact, there is a need for an evaluation of existing methods with respect to older people. In this study, two similar experiments were carried out that focus on focus groups. In addition, the use of personas as a tool in elicitation was explored. The purpose of using personas in the study was to personalize and engage the users into discussion where they were able to be more open in providing feedback about mobile phone usage. Personas were also used in order to get better understanding and information about the strengths of the methods used in this study.